Penerapan Metode Multi-Objective Optimization On The Basis Of Ratio Analysis Dalam Sistem Pendukung Keputusan Penilaian Kinerja Pegawai Klinik Kecantikan - Dewi Yohana br Ginting; Surizar Rahmi Danur; Dito Putro Utomo; Eka Feby Ronauli Lubis; Sri Novida Sari; Dini Rizqi Dwikunti Siregar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The research conducted is to conduct an employee performance assessment process at a Beauty Clinic. The employee performance assessment process at a Beauty Clinic is carried out to provide awards to qualified employees at the Beauty Clinic. This study applies a Decision Support System (DSS) which is used as a system that can process employee performance assessments at the Beauty Clinic. In the employee performance assessment process at the Beauty Clinic, there are 6 criteria, namely Service Orientation, Integrity, Responsibility, Initiative, Discipline and Attendance. Thus, a system is needed that can make decisions, namely DSS by implementing the MOORA method to obtain preference values ​​from employee performance assessments at the Beauty Clinic, there is the best alternative in alternative A5 with a preference value of 0.37472